Espessura corneana mensurada pelo paquímetro ultra-sônico e pelo microscópio especular Topcon SP-2000P em gatos - Ranzani, José Joaquim Titton [UNESP]; Mobricci, L. A. L. [UNESP]; Brandão, Claudia Valeria Seullner [UNESP]; Chiurciu, J. L. V. [UNESP]; Cremonini, D. N. [UNESP]; Rodrigues, G. N. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
Avaliou-se a espessura corneana central de 13 gatos normais com microscópio especular de não-contato Topcon SP-2000P e paquímetro ultra-sônico. Foi observado aumento da espessura corneana mensurada pelo paquímetro ultra-sônico comparado ao microscópio especular.

The central corneal thickness of 13 normal cats was evaluated by a Topcon SP-2000P noncontact specular microscope and by an ultrasonic pachymetry was evaluated. An increase on the corneal thickness measured by ultrasonic pachymetry as compared to the specular microscope was observed.
Corneal thickness measured by ultrasound pachymeter and by Topcon SP-2000P specular microscope Topcon SP-2000P in cats
Keywords: gato; espessura corneana; paquimetria; especular; cat; corneal thickness; pachymetry; specular